Redesign Process of Job Analysis and Job Satisfaction: A Qualitative Study on the Combined Group on Farmer (Gapoktan) - Muafi, Muafi; Wijayani, Ari (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2015)
The purpose of this study is to understand the impact of the need to redesign the position of Gapoktans management towards job satisfaction. This research is a survey research using qualitative approach. The data were collected using interviews, photos, and notes in the field. Populations in this research are stakeholders (Gapoktan committee, farmers, government) who also become a key participant in Hargobinangun, Kaliurang Sleman Daerah istimewa Yogyakarta. The Gapoktan committees participant is 5 person, the government is 3 person, and farmers group is 4 person. The result conclude that a position can be redesigned if the job in that position was used to improve the work method, minimize failure and mistakes, eliminate the work load handling that is unnecessary and work duplication, reduce the fatigue, improve the responsibility, and eventually can increase job satisfaction of the management. All of that can be analyzed by job description and job specification which attached to of each management so that eventually the job satisfaction of the management can be improved.